2022
DOI: 10.3390/met12111813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fracture Properties of Two Metallic Materials under Hydrogen Gas Conditions by Using XFEM

Abstract: Interest in hydrogen energy is increasing due to its eco-friendliness and ease of use. Research is being conducted to produce and use hydrogen in various fields such as hydrogen vehicles and nuclear power plants. However, considering the purity requirements and the need for containment, experiments with hydrogen have several constraints, such as accounting for the charging and purging time. In this study, the effects of hydrogen gas on the fracture properties of T6 heat-treated 6061 aluminum alloy (Al6061-T6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…For an aluminum alloy sample, Gairola and Jayaganthan [51] correctly predicted the material fracture toughness, suggesting that 3D XFEM simulations are slightly better than 2D. Kim et al [58] showed the effects of hydrogen gas on the fracture behavior of an aluminum alloy by simulating fracture resistance curves of compact tension specimens. The XFEM load and displacement curves were within 5% of the experimental conditions.…”
Section: Xfem and Compositesmentioning
confidence: 99%
“…For an aluminum alloy sample, Gairola and Jayaganthan [51] correctly predicted the material fracture toughness, suggesting that 3D XFEM simulations are slightly better than 2D. Kim et al [58] showed the effects of hydrogen gas on the fracture behavior of an aluminum alloy by simulating fracture resistance curves of compact tension specimens. The XFEM load and displacement curves were within 5% of the experimental conditions.…”
Section: Xfem and Compositesmentioning
confidence: 99%
“…To model the initial crack and crack propagation in Abaqus/CAE using the XFEM method, it is necessary to adopt the linear traction–separation law. This law is characterized by three parameters: cohesion force, cohesion energy, and critical displacement [ 15 ]. The evolution of the fracture is modeled according to three specific stress-based criteria: maximum principal stress (MAXPS), maximum nominal stress (MAXS), quadratic nominal stress (QUADS).…”
Section: Computational Modellingmentioning
confidence: 99%
“…It is also modeled on three criteria specifically based on strain: maximum principal strain (MAXPE), maximum nominal strain (MAXE), and quadratic nominal strain (QUADE). In the literature [ 15 , 20 ], we find that several studies are based on the MAXPS criterion to model the initiation and propagation of the crack. In our study, we based our analysis on the maximum nominal stress (MAXPS) and critical displacement.…”
Section: Computational Modellingmentioning
confidence: 99%
See 1 more Smart Citation